Let me sing your songs: how Finns found xöömei - Heikkilä, Sauli (The New Research of Tuva, 2017)
The author of this essay, musician and founder of the Throat Singing Association of Finland (1997), tells the story of how an association of throat singing practitioners came to be in Finland, and how to teach this art to those wishing to learn it. The story also covers the author’s own musical preferences and his life-changing visit to a week-long workshop led by Boris Salchak from Tuva in 1995. Two years later, the author and other aficionados of Tuvan xöömei founded the Throat Singing Association and started holding festivals featuring invited Tuvan singers and throat singing courses. The author describes his collaboration with renowned Tuvan performers, as well as throat singing scholars from the USA, the Netherlands, UK, Italy, etc. The author holds that throat (or overtone) singing is a special sound practice. Tuvan practices can be compared with similar techniques developed by indigenous peoples of Africa, North America, Japan and Tibet. Throat singing as a practice is closely linked to specific ancient worldviews of peoples and cultures living close to nature. Finns are also considered living in close proximity to nature, which may explain their partiality to throat signing. Dozens actively practice xöömei and hundreds have experienced it, which is a much larger percentage than in other European states. In the essay, the author also focuses on the throat singing courses he has been giving for a while and shares his observations of his students, their motivation, specific training techniques and adapting them to the desires and intentions of his students. He believes that almost everybody can learn singing, and most people can have a command of throat singing. The essay also covers the main problems that aspiring throat singers can face, as well as specific styles of the xöömei, concluding with the idea that it is impossible to master throat singing in a short period of time. The key to success is only found in regular and extensive practice.